Job Satisfaction: The Role of Job Involvement, Job Characteristics, and Organizational Commitment at PT Adimulia Palmo Lestari Batang Hari - Mudrikah; Kurniawan, Ignatius Soni Kurniawan (Jurnal Bisnis dan Manajemen, 2025)
This study investigates the complex interplay between job involvement, job characteristics, and organizational commitment as determinants of job satisfaction within a specific industrial context. Utilizing a sample of 85 employees from PT Adimulia Palmo Lestari, a palm oil company in Batang Hari, Indonesia, this research employed a quantitative survey design and Partial Least Square (PLS-SEM) analysis. The finding reveal that job involvement did not have a significant impact on organizational commitment. In contrast, job characteristics were proven to have a significant impact on organizational commitment. In addition, job involvement significantly influenced job satisfaction, as well as there was a significant relationship between job characteristics and job satisfaction. Likewise, organizational commitment was also found to have a significant relationship with job satisfaction. However, job involvement did not act as a mediator of job satisfaction, which challenges the theoretical assumption of the central role of job involvement, while job characteristics through organizational commitment significantly influenced job satisfaction. These findings indicate that for companies, job satisfaction is more influenced by job characteristics than job involvement, which indicates the limited role of job involvement as assumed in theory. Furthermore, job characteristics need to be strengthened through clarity of responsibilities, autonomy, and feedback, as these have been shown to increase commitment and job satisfaction. Strengthening organizational commitment can be achieved through reward programs and career development, which can then boost employee job satisfaction and reduce turnover rates.